2018
DOI: 10.1016/j.oceaneng.2018.04.073
|View full text |Cite
|
Sign up to set email alerts
|

New shape function solutions for fracture mechanics analysis of offshore wind turbine monopile foundations

Abstract: Offshore wind turbines are considered one of the most promising solutions to provide sustainable energy. The dominant majority of all installed offshore wind turbines are tied up to the seabed using monopile foundations. To predict the lifetime of these structures, reliable values for shape function and stress intensity factor are needed. In this study, finite element simulations have been performed for a wide range of monopile geometries with different dimensions, crack lengths as well as depths to evaluate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…where a is the crack length, N is the number of cycles, ∆K is the SIF range, and C and m are material constants. State-of-the-art numerical and experimental research on bilinear crack-growth law phenomena can be found in [70][71][72][73][74][75][76][77][78][79]. The safety margin for fatigue reliability analysis based on LEFM (Linear Elastic Fracture Mechanics) is given by:…”
Section: Probabilistic Fatigue and Fracture Mechanics Approachesmentioning
confidence: 99%
“…where a is the crack length, N is the number of cycles, ∆K is the SIF range, and C and m are material constants. State-of-the-art numerical and experimental research on bilinear crack-growth law phenomena can be found in [70][71][72][73][74][75][76][77][78][79]. The safety margin for fatigue reliability analysis based on LEFM (Linear Elastic Fracture Mechanics) is given by:…”
Section: Probabilistic Fatigue and Fracture Mechanics Approachesmentioning
confidence: 99%
“…Foundation structure acts as a life‐limiting component for an OWT as it is subjected to a spectrum of structural loads, such as weight of the rotor and nacelle assembly, bending load from wind, wave currents, and vibrations due to rotor blades. Most of the installed OWTs consist of monopile foundations which are built by stacking 3 to 7 m diameter cylindrical sections of 30 to 125 mm thickness and can cost up to 35% of the total set‐up cost of an OWT 25–27 . Besides, the circumferential weldments joining the thick monopile sections lead to material property variations at the WM‐HAZ‐BM interface, which turns into a favorable site for fatigue crack initiation.…”
Section: Introductionmentioning
confidence: 99%
“…To model the floating structural support system failure, Bocher et al 17 proposed the application of fracture mechanics with a modified shape function for failure criteria prediction. This approach was applied to a monopile structure, and it captures the stress intensity factors and their dependence characteristic reliably.…”
Section: Introductionmentioning
confidence: 99%